Motivation toward Students' English Achievement - Syaveny, Niza; Johari, Indra (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
This study aims to determine the relationship of motivation (X) on students’ English learning achievement (Y) of Senior High School number 12 Padang. The population of this research was students of Senior High School number 12 Padang with total population was 894 students. Sample was selected by stratified random sampling technique with total sample was 100 students. The data were collected by using questionnaire. The data were analyzed by using quantitative descriptive technique with SPSS computer program version 20. Based on result of data analysis it can be found that there is a positive correlation between X and Y high category (0,783) and significance value less than 0,05 (0,000 <0,05). It can be said that the motivated students make learning achievement better. Thus, internal and external students’ motivation should be considered by the educationist practice.